Distribución espacial de Collaspidia sp (Coleoptera, Chrysomelidae) en el cultivo de papa. - Corral, A.; Gómez, M.; Pagnone, T. (Semiárida, 2020)
Distribución espacial de Collaspidia sp (Coleoptera, Chrysomelidae) en el cultivo de papa.